Research methods in applied linguistics - Dornyei, Zoltan (Oxford University, 2011)
What is research and how does this book approach it? -- Qualitative, quantitative, and mixed methods research -- Quality criteria, research ethics, and other research issues -- Longitudinal verses cross-sectional research -- Quantitative data collection -- Qualitative data collection -- Mixed methods research: purpose and design -- Classroom research -- Quantitative data analysis -- Qualitative data analysis -- Data analysis in mixed methods research -- Writing a quantitative report -- Writing qualitative and mixed methods reports -- How to choose the appropriate research method.; Includes bibliographical references (p. [317]-328) and index